Building innovation capability in SMEs through university-business collaboration - van der Poel, Marcel H; Bakker, Diederich; Rus, Roy (Journal of Management and Business Education, 2024)
Small and medium-sized enterprises (SMEs) often struggle with company innovation, compared to their larger counterparts. A university-business collaboration (UBC) programme in the north of the Netherlands attempts to increase the innovation capabilities of regional SMEs with the support of graduating bachelor students. The 18-months long Hanze Innovation Traineeship Programme (HITP) combines the graduation phase with a consecutive 12-months traineeship, during which students are meant to implement an innovation at the company. We measure the innovation capacity of the participating SMEs at the beginning of the programme and identify strong and weak points within the organisations. We discuss the outcomes of the HITP for SME innovation and further evaluate the programme’s suitability on the intended student learning outcomes.